2023
DOI: 10.3390/su15021721
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Graduate Student Expansion and Innovative Human Capital on Green Total Factor Productivity

Abstract: Using data from 30 provinces and cities in China from 2005–2018, panel regression models, mediation models, quantile regressions and threshold regressions were used to examine the relationship between graduate student size expansion, innovative human capital and green total factor productivity (GTFP) and analyze the influence mechanisms and heterogeneity among them. The results of the study are as follows: First, graduate student expansion and innovative human capital are the driving force for GTFP growth in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The results of intermediate effect test confirm that human capital, as an essential input factor in endogenous economic growth theory, helps to improve the efficiency of resource usage [82]. This phenomenon is especially prominent in China, since the expansion of graduate enrollment has greatly contributed to the cultivation of high-level talents, providing great support for the development of a green economy [83]. It is also confirmed that human capital in China has spatial agglomeration and spillover effects, which makes production greener and is thus conducive to a green economy [84].…”
Section: Discussionmentioning
confidence: 87%
“…The results of intermediate effect test confirm that human capital, as an essential input factor in endogenous economic growth theory, helps to improve the efficiency of resource usage [82]. This phenomenon is especially prominent in China, since the expansion of graduate enrollment has greatly contributed to the cultivation of high-level talents, providing great support for the development of a green economy [83]. It is also confirmed that human capital in China has spatial agglomeration and spillover effects, which makes production greener and is thus conducive to a green economy [84].…”
Section: Discussionmentioning
confidence: 87%
“…When carbon emissions are taken into account, the GTFP of maize mostly reflects how much the existing inputs of production materials contribute to the output. Based on the current maize production situation in China and the research results of other scholars Xing et al, 2023;Yao et al, 2023), the following indicators were chosen as the factors that affect maize' s GTFP.…”
Section: Selection Of Indicators For Influencing Factorsmentioning
confidence: 99%
“…Benhabib and Spiegel found that total factor productivity depends on human capital accumulation [21]. Yao et al found that the increase in innovative human capital significantly contributes to green TFP, and that the effect on green TFP tends to have a decreasing marginal effect [22].…”
Section: Total Factor Productivitymentioning
confidence: 99%